上海电信长途语音业务市场分析 = An analysis on long-distance voice business market of Shanghai telecom - 夏斌 Xia, Bin (2008)
Identifying various market segments to enhance Shanghai Telecom's market positioning. Assess the competitive landscape of the industry and analyze the relationship between traditional voice business and IP business. Pricing, channel strategy, promotion and advertisement strategy will also be studied.